2017
DOI: 10.1021/acs.jmedchem.7b00274
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Selective Inhibitor of Protein Arginine Deiminase 2

Abstract: Protein arginine deiminase 2 (PAD2) plays a key role in the onset and progression of multiple sclerosis, rheumatoid arthritis and breast cancer. To date, no PAD2-selective inhibitor has been developed. Such a compound will be critical for elucidating the biological roles of this isozyme and may ultimately be useful for treating specific diseases in which PAD2 activity is dysregulated. To achieve this goal, we synthesized a series of benzimidazole-based derivatives of Cl-amidine, hypothesizing that this scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 55 publications
2
86
0
Order By: Relevance
“…In RA, an adverse immune response triggered by anti‐citrullinated protein antibodies (ACPA) leads to abnormal release of PADs into joints, thereby setting up the lethal feedback loop associated with disease pathology . Inhibitors of PADs have been shown to reduce the levels of citrullinated antigens and appear to be a viable therapeutic approach for drug development . Given that there are five PAD isoforms (PADs 1–4 and 6) with unique cellular and tissue expression profiles, how PADs are dysregulated and what specific roles they play in human diseases remain poorly understood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In RA, an adverse immune response triggered by anti‐citrullinated protein antibodies (ACPA) leads to abnormal release of PADs into joints, thereby setting up the lethal feedback loop associated with disease pathology . Inhibitors of PADs have been shown to reduce the levels of citrullinated antigens and appear to be a viable therapeutic approach for drug development . Given that there are five PAD isoforms (PADs 1–4 and 6) with unique cellular and tissue expression profiles, how PADs are dysregulated and what specific roles they play in human diseases remain poorly understood.…”
Section: Methodsmentioning
confidence: 99%
“…[17] Inhibitors of PADs have been shown to reduce the levels of citrullinated antigensa nd appear to be av iable therapeutic approach for drug development. [19] Given that there are five PADi soforms (PADs 1-4 and 6) with unique cellular and tissue expression profiles,h ow PADs are dysregulated and what specific roles they play in human diseases remain poorly understood.S pecific activity-based probes (ABPs)a re thus urgently needed to understand PADf unction in the context of specific tissues at the proteome levels.…”
mentioning
confidence: 99%
“…This led to the development of second-generation inhibitors that were predicated on improving the lipophilicity of the core structure by substituting the C-terminal carboxamide in 1a and 1b with a benzimidazole moiety and the N-terminal phenyl ring with a biphenyl substituent resulting in BB-F-amidine ( 5a ) and BB-Cl-amidine ( 5b ) (Figs. 1d and 2b) (Knight et al 2015; Muth et al 2017). This led to a dramatic increase in the lipophilicity of BB-Cl-amidine (CLogP = 4.17) as compared to Cl-amidine (CLogP = −0.23), which was predicted to aid cell entry (Knight et al 2015).…”
Section: Pad Inhibitorsmentioning
confidence: 99%
“…Consistent with this prediction, BB-Cl-amidine was far superior when compared to Cl-amidine in a variety of cell-based assays and animal models but showed similar in vitro efficacy (Ghari et al 2016; Horibata et al 2015; Kawalkowska et al 2016; Knight et al 2015). Recently, Muth et al reported a detailed SAR for 5a and 5b with a methyl benz-imidazole scaffold that included a lactam ring in place of N-terminal phenyl group (Muth et al 2017). The most potent inhibitors 6a and 6b exhibited excellent PAD2 selectivity (up to 106-fold) and proved to be potent in several cell-based assays (Fig.…”
Section: Pad Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation